Distributed wireless networking with an enhanced physical-link layer interface - Tang, Yanru, author; Luo, Rockey, advisor; Yang, Liuqing, committee member; Pezeshki, Ali, committee member; Wang, Haonan, committee member (Colorado State University. Libraries, 2019)
This thesis focuses on the cross-layer design of physical and data link layers to support efficient distributed wireless networking. At the physical layer, distributed coding theorems are proposed to prepare each transmitter with an ensemble of channel codes. In a time slot, a transmitter chooses a code to encode its messages and such a choice is not shared with other transmitters or with the receiver. The receiver guarantees either reliable message decoding or reliable collision report depending on whether a predetermined reliability threshold can be met. Under the assumption that the codeword length can be taken to infinity, the distributed capacity of a discrete-time memoryless multiple access channel is derived and is shown to coincide with the classical Shannon capacity region of the same channel. An achievable error performance bound is also presented for the case when codeword length is finite. With the new coding theorems, link layer users can be equipped with multiple transmission options corresponding to the physical layer code ensemble. This enables link layer users to exploit advanced wireless capabilities such as rate and power adaptation, which is not supported in the current network architecture. To gain understandings on how link layer users should efficiently exploit these new capabilities, the corresponding link layer problem is investigated from two different perspectives. Under the assumption that each user is provided with multiple transmission options, the link layer problem is first formulated using a game theoretic model where each user adapts its transmission scheme to maximize a utility function. The condition under which the medium access control game has a unique Nash equilibrium is obtained. Simulation results show that, when multiple transmission options are provided, users in a distributed network tend to converge to channel sharing schemes that are consistent with the well-known information theoretic understandings. A stochastic approximation framework is adopted to further study the link layer problem for the case when each user has a single transmission option as well as the case when each user has multiple transmission options. Assume that each user is backlogged with a saturated message queue. With a generally-modeled channel, a distributed medium access control framework is proposed to adapt the transmission scheme of each user to maximize an arbitrarily chosen symmetric network utility. The proposed framework suggests that the receiver should measure the success probability of a carefully designed virtual packet or a set of virtual packets, and feed such information back to the transmitters. Given channel feedback from the receiver, each transmitter should obtain a user number estimate by comparing the measured success probability with the corresponding theoretical value, and then adapt its transmission scheme accordingly. Conditions under which the proposed algorithm should converge to a designed unique equilibrium are characterized. Simulation results are provided to demonstrate the optimality and the convergence properties of the proposed algorithm.